From Intended to Enacted: A Situated Analysis of TPACK-in-Action Through Video-Stimulated Recall in Geometry Classrooms - Umi Hanifah; Masriyah Masriyah; Ayu Silvi Lisvian Sari; Nurus Saadah; Jessica Dwi Nur Cahyani (Riemann: Research of Mathematics and Mathematics Education, 2026)
The integration of digital technology into mathematics classrooms remains inconsistent despite the development of the Technological Pedagogical Content Knowledge (TPACK) framework. This study investigates the persistent "know–do gap" by proposing a conceptual framework consisting of intended, enacted, and reflected TPACK. A qualitative multiple-case study was conducted with four secondary mathematics teachers in East Java, Indonesia. Data were triangulated from lesson plans, dual-camera classroom observations, and video-stimulated recall (VSR) interviews. Findings reveal a significant discrepancy: while teachers designed sophisticated technology-rich lessons, 65% of planned activities were shortened or abandoned during enactment. This regression to traditional instruction was primarily driven by excessive dual cognitive load and real-time classroom management pressures. VSR successfully uncovered teachers’ tacit reasoning, serving as a cognitive trigger for reflective improvement. The study concludes that TPACK is a situated and dynamic competence rather than a static body of knowledge. Implications suggest that professional development should move beyond technical training toward structured video-reflection cycles to develop teachers' adaptive orchestration and real-time decision-making skills.